Not in vain ; 18th what God hath wrought amongst the Kanakas in Queensland being Report of the Queensland Kanaka Mission for the year 1903-1904 : Eighteenth annual report, including Solomon Island Branch (1904)
Contents includes : Queensland Kanaka Mission : Object and principles (revised).
Photocopy.
Keywords: Queensland Kanaka Mission; Brethren movement -- missions -- Australia -- history